Is 39 Week Too Late For Elective Caesarean Section - Salleha Binti Khalid; Muhammad Shamsir Mohd Aris (John Wiley & Sons, Inc., 2024)
Objective: To determine the percentage of emergency caesarean section among patient who came earlier than their elective date and its outcome. Methods: This is a retrospective study. Using the elective caesarean section list, all women who planned to have elective caesarean sections in Hospital Ampang from January the first till 31st December 2015 were in included. Exclusion criteria includes women with comorbid such as hypertensive disease in pregnancy, diabetes in pregnancy, multiple pregnancy, known congenital abnormality and intrauterine growth restrictions. Results: A total of 416 elective caesarean section were schedule in 2015. From this 312/416 (75%) were included in this study. 60/312 (19.2%) came in labour prior to their elective caesarean section date. Among those who came earlier 29/60 (48.3%) presented in labour before 38 week period of amenorrhoea and 31/60 (51.7%) presented between 38 to 39 week. Breech in labour made 60% (36/60) of the main indication for caesarean section followed by 25% (15/60) repeat caesarean section and 15% (9/60) has 2 previous scars. 17/60 (28.3%) had blood loss of >500mls however there were no major postpartum haemorrhage reported. There was no other complications such as extended tear or bladder injury. There were five neonatal admission 5/60 (8.3%) compared to 20/252 (7.9%) among those who had elective caesarean section. The difference were not significant with (p= 0.7944) using a chi-squared test. All the neonates had Apgar score of 7 and above at 1 minute of life. Discussions & Conclusion: There were no significant morbidity to the mother and NICU admission between those who had emergency versus those who had elective caesarean. Almost 20% patients presented earlier than their elective date putting the stress on the oncall team. A larger prospective study is warranted to find the ideal time for elective caesarean section without risking the mother and her neonate.